2022
DOI: 10.2106/jbjs.21.01278
|View full text |Cite
|
Sign up to set email alerts
|

Quality Reporting Windows May Not Capture the Effects of Surgical Site Infections After Orthopaedic Surgery

Abstract: Background: Postoperative surgical site infections (SSIs) and the associated complications impact morbidity and mortality and result in substantial burden to the health-care system. These complications are typically reported during the 90-day surveillance period, with implications for reimbursement and quality measurement; however, the long-term effects of SSI are not routinely assessed. We evaluated the long-term effects of SSI on health-care utilization and cost following orthopaedic surgery in an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The average infection rate of 2% among all patients who received follow‐up in these three studies is much lower than that reported in other studies examining infection rates after similar procedures. For example, post‐surgical infection rates are higher following traumatic injuries treated by ORIF in LMICs (6.4%) [53] and following orthopaedic surgery in the USA (about 4%) [54, 55], perhaps representing a lack of follow‐up and/or under‐reporting within the studies in this review [5, 54, 56]. The discrepancies in these numbers and the high complication rates highlight how outreach organizations have a responsibility to conduct follow‐up or ensure follow‐up is attainable.…”
Section: Discussionmentioning
confidence: 99%
“…The average infection rate of 2% among all patients who received follow‐up in these three studies is much lower than that reported in other studies examining infection rates after similar procedures. For example, post‐surgical infection rates are higher following traumatic injuries treated by ORIF in LMICs (6.4%) [53] and following orthopaedic surgery in the USA (about 4%) [54, 55], perhaps representing a lack of follow‐up and/or under‐reporting within the studies in this review [5, 54, 56]. The discrepancies in these numbers and the high complication rates highlight how outreach organizations have a responsibility to conduct follow‐up or ensure follow‐up is attainable.…”
Section: Discussionmentioning
confidence: 99%
“…Although this limits comparison with the bundle time horizon that other studies have used,43 their results are still applicable to health payers and systems making short-term resource-allocation decisions. Due to their focus on short-term, TJA-specific costs and benefits, the authors also did not consider long-term diabetes-related or other sequelae avoided by screening and treatment, which would further increase the effectiveness of screening 36…”
Section: Discussionmentioning
confidence: 99%
“…Due to their focus on short-term, TJA-specific costs and benefits, the authors also did not consider long-term diabetes-related or other sequelae avoided by screening and treatment, which would further increase the effectiveness of screening. 36…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Surgical site infections (SSIs) are apparent worldwide, with reports that in England, deep wound infection after proximal femoral fracture incurred total costs of treatment per infected case of £24,410 compared with £7210 for patients without infection [ 3 ]. A recent study from the US reported a significant increase in healthcare costs over 16 months due to SSI after orthopedic surgeries, with a 64% increase in the two-year costs due to SSI [ 4 ]. Infections lead to longer hospital stays; in the case of SSI in hip fractures, the mean length of stay of patients was 76 days (50 days for superficial wound infections, 100 days for deep wound infections) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%